Recent advances in multi-photon 3D laser printing: active materials and applications - Mainik, Philipp; Spiegel, Christoph A.; Blasco, Eva (Advanced materials, 2024)
Since the pioneering work of Kawata and colleagues in 1997, multi-photon 3D laser printing, also known as direct laser writing, has made significant advancements in a wide range of fields. Moreover, the development and commercialization of photocurable inks for this technique have expanded rapidly. One of the current trends is the transition from static to active printable materials, often referred to as 4D microprinting, which enables a new degree of control in the printed systems. This review focuses on four primary application areas: microrobotics, optics and photonics, microfluidics, and life sciences, highlighting recent progress and the crucial role of active materials, including liquid crystalline elastomers, hydrogels, shape memory polymers, and composites, among others. It also addresses ongoing challenges and provides insights into the future prospects in the different fields.